2017
DOI: 10.1103/physrevlett.118.017001
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Scattering off Defects and Possible Bound States in Charge-Ordered YBa2Cu3Oy

Abstract: Observing how electronic states in solids react to a local symmetry breaking provides insight into their microscopic nature. A striking example is the formation of bound states when quasiparticles are scattered off defects. This is known to occur, under specific circumstances, in some metals and superconductors but not, in general, in the charge-density-wave (CDW) state. Here, we report the unforeseen observation of bound states when a magnetic field quenches superconductivity and induces long-range CDW order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 83 publications
1
33
1
Order By: Relevance
“…6 (a) and (b) demonstrate that disorder is key to the lineshape asymmetry. We emphasize that the mechanism for this asymmetry is different from that proposed by Zhou et al, 36 who suggested that near-unitary impurity resonances generate an asymmetric LDOS distribution. The scattering potential used in this work is far too weak to generate such resonances, and instead we propose below that its main role is to disorder the CDW, which in turn generates skewed lineshapes.…”
Section: (E) and (F)]contrasting
confidence: 78%
See 2 more Smart Citations
“…6 (a) and (b) demonstrate that disorder is key to the lineshape asymmetry. We emphasize that the mechanism for this asymmetry is different from that proposed by Zhou et al, 36 who suggested that near-unitary impurity resonances generate an asymmetric LDOS distribution. The scattering potential used in this work is far too weak to generate such resonances, and instead we propose below that its main role is to disorder the CDW, which in turn generates skewed lineshapes.…”
Section: (E) and (F)]contrasting
confidence: 78%
“…66 Ref. 36 did indeed find that the left and right linewidths scale with the amount of disorder in the crystal; however, it is also clear that long-range CDW order is prerequisite for this effect, suggesting a different mechanism.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Third, depending on the relative magnitude of the two effects and on which line is considered, the changes in K ( r ) and ν quad ( r ) may, partially or entirely, compensate each other. In YBCO, there are five different lines per 17 O site (nuclear spin I = 5/2) and three per 63 Cu (nuclear spin I = 3/2) and our previous work 28 , 41 has shown how each line shape could be quantitatively understood from the combination of magnetic and quadrupole effects. We have established that the effects of the CDW are better seen on the upper frequency quadrupole satellites of 63 Cu and 17 O, hereafter called HF1 and HF2 respectively (see Methods for details).…”
Section: Resultsmentioning
confidence: 86%
“…O(2) data are lower than those for O(3), which we attribute to a systematic error in the fitting, due to the uncertainty generated by the absence of splitting of the low-frequency satellites. It should be noted that electronic bound states in high fields make the distribution of K values asymmetric [62]. In low field, the vortex lattice also produces an asymmetric distribution of K. Therefore, the Knight shift extracted from the positions of maximum intensity corresponds, strictly speaking, to the mode of the skewed distribution rather than to its mean value.…”
Section: Knight Shift Determinationmentioning
confidence: 99%